Serious games for rehabilitation of stroke patients with vibrotactile feedback - Alamri, A.; Kim, H. N.; Cha, J.; El Saddik, A. (International Journal of Computer Science in Sport, 2010)
In this paper, we present a set of serious games with vibrotactile feedback developed for upper extremity motor function rehabilitation. These games are part of a framework called SIERRA that stands for Post-Stroke Interactive and Entertaining Rehabilitation with ReActive objects. The framework uses Augmented Reality technology to provide natural exercise environment and motivating virtual objects at the same time. It adopts serious games concept to provide patients with a more entertaining environment for treatments. We seamlessly superimpose virtual objects onto a real environment and patients can interact with them in a motivating game scenario. Since vibrotactile actuators are attached to the real objects, patient can experience haptic feedback as well as audiovisual feedback. Usability results show that the serious games with vibortactile feedback offers significant advantages both in terms of improving interests of the subjects for the game and in dealing with the realism of the games.